A new method for assessing food quality in common vole (Microtus arvalis) populations - Jánová, E. (Eva); Bryja, J. (Josef); Čižmár, D.; Čepelka, L.; Heroldová, M. (Marta) (European Journal of Wildlife Research, 2015)
Food quality is an important factor influencing the demography of small rodents. While there have been numerous studies on food supply during small mammal population cycles, studies on quality of food consumed are rare due to technical difficulties in estimating nitrogen in small samples, such as stomachs or faeces. In this study, we use a new method, near infrared reflectance spectroscopy (NIRS), for estimating nitrogenous compounds (NC) in stomachs of common voles (Microtus arvalis). Samples were taken from two populations over two 3-year periods. Vegetation cover (managed alfalfa/set-aside field), and thus also food supply, differed significantly between the two periods. In analysing the effects of food supply and individual attributes (i.e. sex, body size, reproduction) on NC in stomachs, we were able to show that nitrogen varied uniformly and that sex, body size and season had no effect. No significant difference in NC intake was observed between the two study periods, despite individuals being smaller and the population less abundant during the second period. During the peak densities, however, reproducing females consumed food with a significantly higher level of nitrogen than all other individuals. Our results indicate that changes in food supply do not affect the overall quality of food consumed but that maintenance of nutritional quality may require higher energetic release, which may affect body condition. We confirm that NIRS represents a useful new tool opening new possibilities in small-mammal ecology studies.